MECHANIZATION INDEX IN AGRICULTURAL PROPERTIES OF THE REGION OF SINOP – MT, BRAZIL - E. H. Nunes; T. V. Souza; I. B. Zanatto; H. A. Sella; V. Cunico; W. G. Vale (Scientific Electronic Archives, 2016)
Agriculture is an activity of great expansion in the state of Mato Grosso (MT), which reflects on the city of Sinop and proximities, and in an intense way mechanization is intensively applied in these areas. This study aimed to diagnose the level of mechanization (Kw/ha) in relation to the cultivated agricultural area and the total area. To this, a sample of 15 agricultural properties located in the region of Sinop – MT were analyzed. For the scale representation of the properties, 4 strata were applied in function of the property total agricultural area. The availability of power in the property resulted in significant differences in the mechanization index. Stratification was efficient for the determination of the mechanization index in the strata, occurring similarities only between strata 2 (3001 – 5000 ha) and 3 (5001 – 9000 ha). The average participation of the areas analyzed was approximately 50%, in which bigger areas presented inferior participation than smaller areas.